Ethno-linguistic and Toponymic Notes - Zadok, Ran (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
Over fifty individuals bearing Arabian anthroponyms are presented in section A. They lived in Babylonia during the Sargonid, Neo-Babylonian, Achaemenid and early Hellenistic periods. Their names are thoroughly analysed. Section B is a classification and analysis of 170 toponyms from the northeastern corner of the border of Greater Judea with Samaria. Except for few Aramaic ancient survivals, all the toponyms are explicable in Palestinian Arabic terms. Several ancient survivals are discussed in section C.